Biocontrol of Fall Armyworm Larvae by Selected Mexican Metarhizium rileyi Isolates Under Greenhouse and Small-Scale Field Conditions in Maize - Yordanys Ramos; Samuel Pineda-Guillermo; Patricia Tamez-Guerra; Javier Francisco Valle-Mora; José Isaac Figueroa-de la Rosa; Selene Ramos-Ortiz; Luis Jesús Palma-Castillo; Ana Mabel Martínez-Castillo (Insects)
The efficacy of two selected Metarhizium rileyi Mexican isolates (T9-21 and L8-22) against Spodoptera frugiperda was evaluated under greenhouse conditions. To this end, a suspension (1 × 108 conidia/mL) of these isolates was sprayed on maize plants previously infested with six second-instar larvae. No significant differences were observed between the survival curves of the T9-21 and L8-22 isolates. Cadaver sporulation was significantly higher, and the lethal time was significantly lower with the T9-21 isolate compared with those of the L8-22 isolate (97% and 8 days vs. 70% and 10 days, respectively). Based on these results, a small-scale field trial on maize was performed to evaluate the degree of pest control achieved by the T9-21 isolate and compare it with the insecticide spinetoram, applied at a rate of 1 × 1013 conidia/ha and 75 mL/ha, respectively. No significant differences were observed in the proportion of larval mortality between the T9-21 isolate (0.49) and spinetoram (0.72). However, spinetoram significantly reduced natural enemies and phytophagous insect populations compared with the fungus and the control. In conclusion, M. rileyi T9-21 isolate could be a promising alternative for the control of S. frugiperda larvae.